The Effects of Amphiregulin Induced MMP-13 Production in Human Osteoarthritis Synovial Fibroblast. (24th July 2014) - Chen, Yi-Te; Hou, Chun-Han; Hou, Sheng-Mou; Liu, Ju-Fang
Abstract : Osteoarthritis (OA) belongs to a group of degenerative diseases. Synovial inflammation, cartilage abrasion, and subchondral sclerosis are characteristics of OA. Researchers do not fully understand the exact etiology of OA. However, matrix metalloproteinases (MMPs), which are responsible for cartilage matrix degradation, play a pivotal role in the progression of OA. Amphiregulin (AREG) binds to the EGF receptor (EGFR) and activates downstream proteins. AREG is involved in a variety of pathological processes, such as the development of tumors, inflammatory diseases, and rheumatoid arthritis. However, the relationship between AREG and MMP-13 in OA synovial fibroblasts (SFs) remains unclear. We investigated the signaling pathway involved in AREG-induced MMP-13 production in SFs. AREG caused MMP-13 production in a concentration- and time-dependent manner. The results of using pharmacological inhibitors and EGFR siRNA to block EGFR revealed that the EGFR receptor was involved in the AREG-mediated upregulation of MMP-13. AREG-mediated MMP-13 production was attenuated by PI3K and Akt inhibitors. The stimulation of cells by using AREG activated p65 phosphorylation and p65 translocation from the cytosol to the nucleus. Our results provide evidence that AREG acts through the EGFR and activates PI3K, Akt, and finally NF-kappaB on the MMP-13 promoter, thus contributing to cartilage destruction during osteoarthritis.